2015
DOI: 10.4103/0976-7800.165589
|View full text |Cite
|
Sign up to set email alerts
|

Overview of research studies on osteoporosis in menopausal women since the last decade

Abstract: Purpose/Introduction:Osteoporosis is a multifactorial and slowly emerging global health problem. The lifetime risk of dying from hip fracture is same as that from breast cancer. One out of three women between age group of 50-60 years in India suffers from osteoporosis. Indian women have an early age of onset of osteoporosis as compared to western counterparts. There is need for early diagnosis, identification of high-risk groups and prevention and treatment of osteoporosis in the Indian context. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Being men was also negatively associated with osteoporosis in this study. The greater prevalence of osteoporosis among women could be attributed to accelerated bone loss due to estrogen deficiency after menopause [31] and a lower peak bone mass compared to men [32]. An earlier study found a higher prevalence of osteoporosis among Malaysian men (10.6%) than women (8.0%), but the subjects were sampled at a university hospital and older (aged ≥50 years).…”
Section: Discussionmentioning
confidence: 99%
“…Being men was also negatively associated with osteoporosis in this study. The greater prevalence of osteoporosis among women could be attributed to accelerated bone loss due to estrogen deficiency after menopause [31] and a lower peak bone mass compared to men [32]. An earlier study found a higher prevalence of osteoporosis among Malaysian men (10.6%) than women (8.0%), but the subjects were sampled at a university hospital and older (aged ≥50 years).…”
Section: Discussionmentioning
confidence: 99%
“…Menopause decreases women quality of life and declines their health status [4]. The most common symptoms associated with menopause are hot flushes [5], genitourinary problems [6] [7], sexual problems [8], mood changes [9], heart [10] and bone [11] problems.…”
Section: Introductionmentioning
confidence: 99%
“…Menopausal age is an important indicator of subsequent morbidity and mortality in women. Early age at menopause increases the risk of cardiovascular diseases [13], osteoporosis [14], colorectal cancer [15], and decline of cognitive ability [16]. Late age of menopause may increase the risk of endometrial [17], ovarian [18] and breast cancer [19].…”
Section: Introductionmentioning
confidence: 99%
“…A study in Delhi estimated the prevalence of osteoporosis as 24.6% in men and 42.5% in women above 50 years of age. [ 10 ] Another study by Sharma et al . has reported a prevalence of 8.5% in the femoral neck region in men.…”
Section: Introductionmentioning
confidence: 99%